Melatonin as a Repurposed Drug for Melanoma Treatment - Rachana Pathipaka; Anita Thyagarajan; Ravi P. Sahu (Medical Sciences, 2023)
Melanoma is the most aggressive type of skin cancer, with a greater risk of metastasis and a higher prevalence and mortality rate. This cancer type has been demonstrated to develop resistance to the known treatment options such as conventional therapeutic agents and targeted therapy that are currently being used as the standard of care. Drug repurposing has been explored as a potential alternative treatment strategy against disease pathophysiologies, including melanoma. To that end, multiple studies have suggested that melatonin produced by the pineal gland possesses anti-proliferative and oncostatic effects in experimental melanoma models. The anticarcinogenic activity of melatonin is attributed to its ability to target a variety of oncogenic signaling pathways, including the MAPK pathways which are involved in regulating the behavior of cancer cells, including cell survival and proliferation. Additionally, preclinical studies have demonstrated that melatonin in combination with chemotherapeutic agents exerts synergistic effects against melanoma. The goal of this review is to highlight the mechanistic insights of melatonin as a monotherapy or combinational therapy for melanoma treatment.